Caracterização da inovação em modelos de negócios: aplicações no transporte aéreo - Pereira, Bruno Alencar (2015)
In the air transport sector, especially in the airlines, innovation in business models can contribute to the creation of value, competitive advantage and profitability with new possibilities of action in the sector. The proposed research aims to identify the business models adopted by Brazilian airlines and characterize how innovation happens to create value, competitive advantage and profitability by models applied to the sector with the identification and implementation of appropriate indicators not yet exploited to this understanding. The methodology consisted of empirical, exploratory and descriptive research by multi case study with three of the main Brazilian airlines, allowing an investigation to raise significant and holistic characteristics of innovation indicators applied to the business models adopted in the sector. The results show the search paradigm breaks related to the dichotomy of the traditionals models low-cost and full-service toward hybrid business models and perceived the need for a business model that maintains a balance between the services offered, however, no major innovations identified by the supplied value proposition. The conclusion is that in the Brazilian airlines the innovation in business models occur linearly as examples highlighted by the companies, that the perception of them, internal changes in business models are considered major organizational innovations, however, there is no evidence results in large external innovations to the market provided by the business models adopted in a comparative panorama of such airlines.